Marketing Management Best Practices to Increase Sales of Green Tourism Destinations in Developing Countries - Hermyn Benny Hina; Pandu Adi Cakranegara; Ratih Pratiwi; Hery Winoto Tj; Hamirul Hamirul (Universitas Muhammadiyah Sorong, 2023)
This study aimed to gain understanding from a series of published scientific evidence studies that have been released with the problem of best practice management marketing studies to increase sales of green tourism in several developing countries. This study was carried out in a descriptive qualitative manner by reviewing much scientific evidence that has been made public in national and international publications for data published in the last ten years. After getting the data, we review it under the phenomenological approach, where we look at the data, and the volume to answer problems that we believe can answer the problem with the principles of validity and high quality. After reviewing and discussing the findings, we can conclude that the findings include an understanding of green tourism, then the best steps in promoting green tourism by saving the environment but still from a business perspective for sustainability and profits. It is hoped that these findings will color similar studies in the future.